Dynamic Wireless Power Transfer for Logistic Robots - Marojahan Tampubolon; Laskar Pamungkas; Huang-Jen Chiu; Yu-Chen Liu; Yao-Ching Hsieh (Energies, 2018)
The prospect of using robots in warehouses or supply chain processes is increasing due to the growth of the online retail market. This logistic robot is available in the market and uses a battery as energy storage device. However, this battery is large and heavy. Therefore, it needs a long recharging time. Dynamic Wireless Power Transfer (DWPT) can be an alternative to the conventional charging system because of its safety and flexibility that enables in motion charging. DWPT reduces the battery requirement size and capacity. Hence the stored energy can be used effectively for load transportation. A compensation with an inductor and two capacitors in the transmitter side, and a series connected capacitor in the receiver side which is named LCC-S compensation type has the capability to maintain the transmitter current with a fixed frequency operation. It provides less variation of the output voltage in response to the load variation. Moreover, the compensation of the receiver side uses only a single series capacitor which is low-cost. The analysis, modeling, and design procedures are discussed in this paper as well as the hardware implementation and verification of a 1.5 kW maximum power DWPT. The experiment shows the capability of the proposed system and shows maximum efficiency can reach 91.02%.